The Potential of Probiotics: A Review - Carlos Ricardo Soccol; Luciana Porto de Souza Vandenberghe; Michele Rigon Spier; Adriane Bianchi Pedroni Medeiros; Caroline Tiemi Yamaguishi; Juliano De Dea Lindner; Ashok Pandey; Vanete Thomaz-Soccol (Food Technology and Biotechnology, 2010)
Probiotics, live cells with different beneficiary characteristics, have been extensivelly studied and explored commercially in many different products in the world. Their benefits to human and animal health have been proven in hundreds of scientific research. Lactobacillus and Bifidobacterium are the main probiotic groups; however, there are reports on the probiotic potential of Pediococcus, Lactococcus, Bacillus and yeasts. Some of the identified probiotic strains exhibit powerful anti-inflammatory, antiallergic and other important properties. Apart from that, the consumption of dairy and non-dairy products stimulates the immunity in different ways. Various food matrices have been used with probiotics, which are briefly documented. In this review, the history of probiotics, their application in the health and food areas and new trends in probiotic products and processes are presented.